COMPENSATION FOR RAPE - A CASE REPORT (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
The tragic end of the whole episode terminated in the satirical “situation ethics”. Despite the ongoing full-scale investigation by the  police, the father of the girl connived with the rapist, forced her daughter to eat her statement, and she refused to identify the  rapist. In return the father received Rs 200,000/- as “compensation money”, medical evidence was castrated, and the law was  noose hanged on the bough of avarice and greed. The father made his action tailored to fit objective circumstances, the situation.  He had been so full and determined in understanding what was right (for him) that he couldn’t visualize what was good (for her  daughter and the society).
Keywords: Rape; Compensation; Ethics